(3fHY GdehGfY Yf LejY GdLhGeYs - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s; (3CHhGdMSf Jbj GdOjf Ydj Hf YHO GdcGaj Hf Ydj GdSHcj GdCfUGQj GdTGaYj,J (B756 (3g` s
(3ChdgG (B:s
(3hPdc jMJhi Ydi YOI SDGdGJ GdSDGd GdChd de MPaJe ef MO CUhd Gdabg daX GdeYQaI hde JMPahG ef MO Gdabg daX GdYde s
(3BNQgG (B:s
(3hGdQGHYI Efg ef YhGQV GdCdaGX hgj eSFdI NdGajI abO eQJ ai TQM GdeNJUQ adjfXQ Je GdcJGH hGdMeO ddg hUdi Gddg Ydjg hSde s
(3HgG fXGe GdJYbjHIs
(3hgh OaGY Yf cJGHg MLI GdLhGeYs
(3HChd GdcJGH GdCSFdI hGdEYJQGVGJ GdJi hLgJ Edjg Mhd cJGH LejY GdLhGeY s
(3Ke GdELGHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3CUhd Gdabgs